Development of human dendritic cells and their role in HIV infection: antiviral immunity versus HIV transmission - Tsunetsugu-Yokota, Yasuko; Muhsen, Mahmod (Frontiers in Microbiology, 2013)
Although dendritic cells (DCs) represent a small cell population in the body, they have been recognized as professional antigen presenting cells and key players of both innate and acquired immunity. The recent expansion of basic knowledge concerning differentiation and function of various DC subsets will greatly help to understand the nature of protective immunity required in designing acquired immunodeficiency syndrome (AIDS) vaccines. However, human immunodeficiency virus (HIV) not only targets CD4+ T cells but also myeloid cells, including macrophages and DC. When HIV infects DC, its replication is highly restricted in DC. Nevertheless, even a low level of HIV production is sufficient to enhance HIV replication in activated CD4+ T cells, through antigen presentation activity by HIV-infected DC. Considering how antiviral immunity is initiated and memory response is maintained, such efficient DC–T cell transmission of HIV should play an important role in the disturbed immune responses associated with HIV infection. Recently, accessory proteins encoded by HIV have been shown to interact with various proteins in DC, and thereby affect DC–T cell transmission. In this review, we summarize the current understanding about DC biology, antiviral immune responses and DC restriction factors, all of which will be important issues for the development of an effective AIDS vaccine in the future.